1980
DOI: 10.1080/09553008014551451
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity Relationships in the Development of Hypoxic Cell Radiosensitizers

Abstract: The effects of substituting 2-nitroimidazoles with groups carrying basic functions were studied. Prototropic, redox, lipophilicity and protein-binding properties were compared with the efficiency in radiosensitizing hypoxic Chinese hamster V79-379A cells in vitro and the cytotoxicities of the compounds after chronic aerobic exposure. Seventeen compounds were (2-nitro-1-imidazolyl)alkylamines in which the effects of changes in the terminating base and of alkyl chain length were investigated. About an order of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 8 publications
0
30
0
1
Order By: Relevance
“…Although, compared with MISO, it exhibits similar or slightly greater radiosensitization of hypoxic cells (Adams et al, 1979;Anderson & Patel, 1979), the clinical potential of benznidazole in cancer treatment is as a chemosensitizer, particularly in combination with CCNU. We have shown that to obtain a given enhancement of tumour response to CCNU the benznidazole dose required is much lower than that for misonidazole (Workman & Twentyman, 1982); moreover, the tumour enhancement is greater than that seen in normal tissues and the therapeutic gain with low dose benzidazole is similar to that with high dose MISO .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, compared with MISO, it exhibits similar or slightly greater radiosensitization of hypoxic cells (Adams et al, 1979;Anderson & Patel, 1979), the clinical potential of benznidazole in cancer treatment is as a chemosensitizer, particularly in combination with CCNU. We have shown that to obtain a given enhancement of tumour response to CCNU the benznidazole dose required is much lower than that for misonidazole (Workman & Twentyman, 1982); moreover, the tumour enhancement is greater than that seen in normal tissues and the therapeutic gain with low dose benzidazole is similar to that with high dose MISO .…”
Section: Discussionmentioning
confidence: 99%
“…see Workman, 1980b and1983). Although similar in electron affinity (redox potential) benznidazole is considerably more lipophilic (Adams et al, 1979), and lipophilicity has a major effect on nitroimidazole pharmacokinetics (see Workman, 1982b Raaflub & Ziegler (1979) and Raaflub (1980) We have shown recently that for the combination of CCNU with misonidazole a major mechanism appears to involve the inhibition of CCNU metabolism by the sensitizer, probably in the liver, resulting in elevated CCNU concentrations in tumour but not normal tissues , 1984a. Benznidazole slows CCNU clearance at much lower doses than misonidazole (Lee & Workman, 1984b), is a considerably more potent inhibitor of drug metabolising enzymes in vivo and exhibits more powerful inhibition of CCNU hydroxylation by liver microsome preparations in vitro (Lee & Workman, unpublished): this explains the comparative potency of benznidazole as a chemosensitizer with CCNU.…”
Section: Discussionmentioning
confidence: 99%
“…3 )h of the The mean NCV in control animals of )ulse i'S a 39.6J 1 7 mi/s was significantly higher than id as the the velocity reported in a previous experit be con-ment (Hirst et al, 1978) and this is attriseries of buted to sex and age differences in the ion had to mice used (12-15-week-old females in the ted nerve present study and 5-6-week-old males in group of the previous experiment). The magnitude tempera-and time course of the reduction in NCV placed in after misonidazole did not differ signi- Table) than would be predicted from its in vitro cytotoxicity (Adams et at., 1978b). Animals tested 12 h after only 4 injections, showed a severe reduction in NCV (to 69% of saline control).…”
mentioning
confidence: 88%
“…Consequently, 4 drugs with differing octanol/water partition coefficients were selected for the present study (Table). For structural formulae see Adams et al (1978a). The reduction potentials of the 3 2-nitroimidazoles are very similar; metronidazole, a 5-nitroimidazole, has a higher reduction potential, i.e.…”
mentioning
confidence: 99%
“…2-Nitroimidazole derivatives, such as misonidazole and etanidazole, have been reported to have potent radiosensitising ability (Sheldon et al, 1974;Brown et al, 1981), and have been clinically studied regarding their application in the radiotherapy of patients with malignant tumours (Chang et al, 1998;Grigsby et al, 1999). The efficiencies of nitroimidazoles as hypoxic radiosensitisers depend on the selective and irreversible binding to the reactive metabolite of the nitro group having one-electron reduction potentials to target molecules in hypoxic tumour cells (Adams et al, 1979). Although nitroimidazole derivatives have been developed as radiosensitisers, they also show preferential toxicity to hypoxic cells as hypoxic cytotoxins (Stratford and Stephens, 1989;Papadopoulou et al, 1996).…”
mentioning
confidence: 99%